2017
DOI: 10.1142/s021974991750037x
|View full text |Cite
|
Sign up to set email alerts
|

2-qubit quantum state transfer in spin chains and cold atoms with weak links

Abstract: In this paper we discuss the implementation of 2-qubit quantum state transfer (QST) in inhomogeneous spin chains where the sender and the receiver blocks are coupled through the bulk channel via weak links. The fidelity and the typical timescale of the QST are discussed as a function of the parameters of the weak links. Given the possibility of implementing with cold atoms in optical lattices a variety of condensed matter systems, including spin systems, we also discuss the possible implementation of the discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…Perturbative couplings have been used in several settings, from quantum-state transfer to entanglement generation. However, previous works focused mainly on one-excitation transfer [28,29,30], with some exceptions dealing with two-excitation transfer [24,25,31]. The case of n > 2 excitation transfer has not yet been addressed in the perturbative regime.…”
Section: Pp-transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Perturbative couplings have been used in several settings, from quantum-state transfer to entanglement generation. However, previous works focused mainly on one-excitation transfer [28,29,30], with some exceptions dealing with two-excitation transfer [24,25,31]. The case of n > 2 excitation transfer has not yet been addressed in the perturbative regime.…”
Section: Pp-transfermentioning
confidence: 99%
“…Now, before dealing with the case n s > 2, we first discuss some of the results obtained in Ref. [24] for the case of two-excitation transfer. Our previous discussion about the n s 1 2 3 4 n w 2l 2l + 1 3l 3l + 1 3l + 2 4l 4l + 1 4l + 2 4l + 3 5l 5l + 1 5l + 2 5l + 3 5l + 4 n res 0 1 0 0 2 0 1 0 3 0 0 0 4 Table 1.…”
Section: Many-body Dynamicsmentioning
confidence: 99%
“…In such a case, it has been shown that two-qubit quantum state transfer [15,26] as well as entanglement generation of two Bell states [27] is achieved with high fidelity. Modifications of the one-dimensional geometry have been investigated too.…”
Section: The Modelmentioning
confidence: 99%
“…While a great amount of work has been devoted to the routing of the quantum state of a single qubit [4][5][6][7][8][9][10][11][12], where the fidelity of the transfer protocol can be expressed in terms of the transition amplitude of a single excitation between a sender and a receiver location [13], the routing of a multiple qubit state is a far less investigated scenario. Although several protocols have been proposed both for two-qubit and multi-partite entangled quantum state transfer [14][15][16][17][18][19][20][21][22][23], their extension to a routing configuration on an arbitrary network is not straightforward. One reason being that almost all the proposed protocols rely on the quantum channel possessing mirror-symmetry, which, allowing for multiple receivers at arbitrary positions, is difficult to attain: in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…While a great amount of work has been devoted to the routing of the quantum state of a single qubit [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], where the fidelity of the transfer protocol can be expressed in terms of the transition amplitude of a single excitation between a sender and a receiver location [ 12 ], the routing of a multiple qubit state is a far less investigated scenario. Although several protocols have been proposed both for two-qubit and multi-partite entangled quantum state transfer [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], their extension to a routing configuration on an arbitrary network is not straightforward. One reason being that almost all the proposed protocols rely on the quantum channel possessing mirror-symmetry, which, allowing for multiple receivers at arbitrary positions, is difficult to attain: in Ref.…”
Section: Introductionmentioning
confidence: 99%